PTH-059 Faecal calprotectin identifies non responders to anti-tnfΑ therapy when measured after induction in inflammatory crohn's disease. (22nd June 2015) - Pavlidis, P; Cavazza, A; Siddique, N; Stamoulos, P; Tumova, J; Medcalf, L; Chung-Faye, G; Dubois, P; Bjarnason, I; Hayee, B
Abstract : Introduction: Poor response to anti-TNFα treatment in patients with Crohn's disease (CD) is not infrequent. As new biologic therapies targeting other immune pathways of the intestinal inflammation are becoming available in routine clinical practice early prognostic markers of treatment failure are urgently needed. Faecal calprotectin (fcal) has been shown to be a useful prognostic marker of relapse in CD correlating well with both endoscopic and magnetic resonance imaging scores. Furthermore, a recently published study utilising gene expression profiling by micro arrays to detect prognostic markers of early response to anti-TNFα therapy identified the two genes coding for the calprotectin subunits (S100A8, S100A9) to be among the most highly expressed gene transcripts in non-responders. Method: This is a retrospective observational study of a prospectively kept database testing the hypothesis that a faecal calprotectin measurement after anti-TNFα induction (infliximab: 8–12 weeks, adalimumab: 6-weeks) reflects response to treatment. CD patients, who commenced anti-TNFα therapy for active, inflammatory disease and had serial fcal measurements before and after induction were identified. Remission was assessed at 6 months and defined as the composite of Harvey Bradshaw Index (HBI < 5) and fcal <250 μg/g. Results: We identified 26 patients who started either infliximab (16) or adalimumab (10) and had serial fcal at the set time points [median age: 32, disease duration: 5 (3, 8), location: 17 ileocolonic, 8 colonic and 1 ileal]. Patients on infliximab received 5mg/kg doses at 0, 2, 6 and then 8 weekly. Those on adalimumab had one dose of 160mg followed by 80 mg after two weeks and then received 40 mg doses fortnightly. At 6 months, 15/26 (58%) patients were in remission. Fcal post induction in those in remission at 6 months was lower compared to those with persistently active disease [65 (38, 118) vs. 269 (161, 542)]. Receiver operator characteristic curve analysis shows that fcal >150 has 93% sensitivity and 91% specificity in predicting non responders (likehood ratio: 10.27, area under curve: 0.98, p < 0.0001). HBI and fcal levels before anti-TNFα induction did not differ between patients with the two different outcomes. Conclusion: Fcal measurement soon after anti-TNFα induction predicts non-response providing the opportunity to identify those patients who require further treatment tailoring early. Disclosure of interest: None Declared.